Language politicies and the politics of language practices essays in honor of Sjaak Kroon / Massimiliano Spotti, Jos Swanenberg, Jan Blommaert, editors. - Spotti, Massimiliano, 1974-; Swanenberg, Adrianus Petrus Cornelis, 1968-; Blommaert, Jan; Kroon, Sjaak (Language policy (Monographic series), 2021)
This edited volume consists of chapters celebrating the career of scholar Sjaak Kroon, who has produced ground-breaking work in the field of ethnography of education, immigrant minority language teaching and language politics. The chapters cover the use of immigrant minority languages in education and the development of policies at all levels and across the globe in this sometimes over-policed field. It particularly focuses on language policy analysis in which both the top-down institutional and the bottom-up ethnographic dimensions are blended, and in which globalization is the main macro-perspective. The chapters describe sensitive tools for investigating, unravelling and understanding the grey space connecting formal language policies to informal politics and practices of language on the ground.